Investigation of Magnetic Circuit Permanent Magnet – Terfenol-D – Air - Bansevicius, R.; Grigaliunas, V.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2008)
Magnetostrictive properties of Terefenol-D can be used for a nanometer creation. There was investigated the magnetic field created by permanent magnet distribution in terfenol-D strip and its variation when reciprocal position between permanent magnet and terfenol- D is varied. The finite element method was used. The reciprocal position was varied by three different modes. The greatest absolute value of magnetic flux density can be obtained when the permanent magnet is situated inside cylinder manufactured of terfenol-D. The greatest ratio of magnetic flux density relative variation to distance between permanent magnet and terfenol-D deviation is obtained, when the terfenol-D strip in situated over the permanent magnet. The magnetic flux is distributed very unevenly inside terfenol-D in this case. Magnetic flux is distributed evenly in terfenol-D when the magnet and terfenol-D are situated parallel one to other, but ratio of magnetic flux density relative deviation to distance deviation is the smallest in this case. Ill. 7, bibl. 3. (in English; summaries in English, Russian and Lithuanian).